2020
DOI: 10.1080/21532974.2020.1781000
|View full text |Cite
|
Sign up to set email alerts
|

Course design features influencing preservice teachers’ self-efficacy beliefs in their ability to support students’ use of ICT

Abstract: This study explores how using action plans, SMART goals, personal learning networking and peer teaching in a first-year education technology course influence pre-service teachers' (PSTs') self-efficacy beliefs in their technological pedagogical knowledge (TPK) and technological content knowledge (TCK). Pre-and post-course survey items from the Teaching Teachers for the Future project were administered to examine PSTs' judgements of their self-efficacy to support students' use ICT in the classroom, including di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The lack of explicit pedagogical strategies to make connections to targeted curricular concepts was also not explicit in the self-guided intervention and may have contributed to PSTs smaller gains in confidence to use robotics in their future teaching. It has been shown that when PSTs are exposed to structured, hands-on learning experiences with robotics that have strong connections to the K-12 curriculum, PST confidence to teach with robotics increased (Martin et al, 2020;Schina et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of explicit pedagogical strategies to make connections to targeted curricular concepts was also not explicit in the self-guided intervention and may have contributed to PSTs smaller gains in confidence to use robotics in their future teaching. It has been shown that when PSTs are exposed to structured, hands-on learning experiences with robotics that have strong connections to the K-12 curriculum, PST confidence to teach with robotics increased (Martin et al, 2020;Schina et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The findings showed that self efficacy towards educational robotics such as PSTs skills and knowledge about how to use robotics for classroom instruction and for teaching science improved after participation in the ER training module. In another study,Martin et al (2020) explored ECE and Primary Education PSTs self-efficacy beliefs to use appropriate technology including robotics in teaching in a technology course at an Australian university. A sample of 92 participants completed a pre-post self efficacy survey.…”
mentioning
confidence: 99%
“…A previous study with first-year PSTs (Martin et al, 2020) used an innovative course design that aimed to enhance their TPACK confidence. The innovative course design included an online technology skills audit and assessment tasks comprising action plans, SMART goals, personal learning networking, and peer teaching.…”
Section: Introductionmentioning
confidence: 99%
“…The findings were based on a 12-item confidence survey conducted pre-and post-course. In the discussion of the findings, Martin et al (2020) made several proposals for improving education technologies coursework to support the development of PSTs' TPACK. One suggestion was that PSTs' TPACK confidence could be further developed by providing experiences for them to demonstrate knowledge of a range of specific technologies used for teaching and learning in creative ways.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as other authors [8,9] indicated, students' motivation and self-concept may also be increased by including digital tools in peer tutoring activities. Although several studies have contributed to the literature in the field and the potentiality of this combination has been strengthened, most authors argue that this field of study is still underdeveloped [10][11][12][13][14].…”
mentioning
confidence: 99%